Building sustainable information systems : proceedings of the 2012 international conference on information systems development - Fisher, Julie; Barnden, Andrew; Barry, Chris; Lang, Michael; Schneider, Christoph (Springer US Imprint: Springer, 2013)
This volume is the collected proceedings of the 21st International Conference on Information Systems Development (ISD2012) held at the Monash University Centre in Prato, Italy. The theme of the conference focused on the significant contribution that information systems can make to challenges posed by the degradation of the natural environment. This contribution includes the role of information systems in mitigation and adaptation strategies as well as addressing the direct contribution of information and communications technology to that degradation. ISD2012 follows the conference series in exploring the relations between research, industry practice and education. Information systems development is at the core of the academic discipline of information systems and the papers in this volume reflect on established topics in information systems development as well as emerging concepts, approaches and practices. This is reflected in the conference tracks including: The Changing Landscape of Information Systems: Properties of a New IS Ecology Methodologies for Design within Complex Environments Green IS - Information Systems for Sustainability Model-driven Engineering in ISD Sustainable ISD Project Management Sustainable Knowledge Management